2014
DOI: 10.1071/an11323
|View full text |Cite
|
Sign up to set email alerts
|

Reproductive performance in the Sheep CRC Information Nucleus using artificial insemination across different sheep-production environments in southern Australia

Abstract: The present paper covers reproductive performance in an artificial-insemination (AI) program of the Sheep CRC Information Nucleus with 24 699 lambs born at eight locations in southern Australia across five lambings between 2007 and 2011. Results from AI with frozen semen compared well with industry standards for natural mating. Conception rates averaged 72%, and 1.45 lambs were born per ewe pregnant for Merino ewes and 1.67 for crossbreds. Lamb deaths averaged 21% for Merino ewes and 15% for crossbreds and 19%… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
34
0
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 60 publications
(41 citation statements)
references
References 21 publications
5
34
0
2
Order By: Relevance
“…The greater lamb mortality for very light or very heavy lambs in the present study agrees with previous results in the United States (Smith, 1977), Australia (Geenty et al, 2014) and the United Kingdom (Sawalha et al, 2007) sheep populations and is also consistent with the reported optimum birth weight of 3.0 to 5.5 kg to avoid the requirement for assisted lambings and mortality (Nowak and Poindron, 2006;Speijers et al, 2010). Greater lamb mortality in light lambs has been attributed to hypothermia, lack of fat reserves and mismothering (Morris et al, 2000;Nowak and Poindron, 2006); poorer ewe uterine contractions for lambs of low birth weight results in slower parturition (Dalton et al, 1980), which may also result in greater lamb mortality.…”
Section: Birth Weightsupporting
confidence: 83%
See 1 more Smart Citation
“…The greater lamb mortality for very light or very heavy lambs in the present study agrees with previous results in the United States (Smith, 1977), Australia (Geenty et al, 2014) and the United Kingdom (Sawalha et al, 2007) sheep populations and is also consistent with the reported optimum birth weight of 3.0 to 5.5 kg to avoid the requirement for assisted lambings and mortality (Nowak and Poindron, 2006;Speijers et al, 2010). Greater lamb mortality in light lambs has been attributed to hypothermia, lack of fat reserves and mismothering (Morris et al, 2000;Nowak and Poindron, 2006); poorer ewe uterine contractions for lambs of low birth weight results in slower parturition (Dalton et al, 1980), which may also result in greater lamb mortality.…”
Section: Birth Weightsupporting
confidence: 83%
“…A combination of management and environmental factors has previously been documented to be associated with lambing difficulty and lamb mortality in the United Kingdom (Wiener et al, 1983;Dwyer et al, 1996), New Zealand (Morris et al, 2000;EverettHincks et al, 2005), Australia (Geenty et al, 2014) and the United States (Gama et al, 1991;Southey et al, 2004) sheep populations. No study has to date examined the association between lambing difficulty and mortality and risk factors in a series of simple regression models and multiple regression models across a diverse sheep population.…”
Section: Discussionmentioning
confidence: 99%
“…Mortality rates in this study were within the range of those previously reported for both twin-(8.1% to 26.7%) and tripletborn (12.7% to 53.4%) lambs managed under extensive pastoral systems in New Zealand [2,17]. The relationship between the sex of the lamb [18] and a curvilinear relationship of lamb birth weight [19,20] with survival to weaning were also consistent with previous work. Interestingly, data from the present study suggests that at low birthweights triplet lambs have lower survival than twins but this is not seen at heavier birth weights.…”
Section: Discussionsupporting
confidence: 90%
“…The IN consisted of 8 genetically linked flocks located in each of the major sheep growing areas of Australia (Armidale, NSW; Trangie, NSW; Cowra, NSW; Rutherglen, VIC; Hamilton, VIC; Struan, SA; Turretfield, SA; and Katanning, WA) and managed by Sheep CRC partner organizations. The design of the IN, including procedures used to select the sires to artificially inseminate the founding dams and the management procedures, have been described Geenty et al, 2014). All sires were used at 2 sites (Armidale and Katanning) and at least 50% of the sires were used at all the sites.…”
Section: Animalsmentioning
confidence: 99%